2019
DOI: 10.1162/jocn_a_01383
|View full text |Cite
|
Sign up to set email alerts
|

Top–Down Attention Is Limited Within but Not Between Feature Dimensions

Abstract: In natural vision, processing of spatial and nonspatial features occurs simultaneously; however, the two types of attention in charge of facilitating this processing have distinct mechanisms. Here, we tested the independence of spatial and feature-based attention at different stages of visual processing by examining color-based attentional selection while spatial attention was focused or divided. Human observers attended to one or two of four fields of randomly moving dots presented in both left and right visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 63 publications
(91 reference statements)
2
28
4
Order By: Relevance
“…Thus, at least for neural pathways contributing to this cluster, the spread of luminance‐based attention was not restricted by surface boundaries. Similar patterns of attentional coselection were previously shown for combinations of space and color (Adamian, Slaustaite, & Andersen, ; Andersen et al, ; Hayden & Gallant, ) and orientation and color (Andersen et al, , ). Together, these findings strongly suggest that attentional facilitation is applied independently to the different task‐relevant dimensions or features that define the target stimulus, with the multiplicative effects of attention to each feature summing to produce maximal enhancement of the SSVEP to the target feature combination.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, at least for neural pathways contributing to this cluster, the spread of luminance‐based attention was not restricted by surface boundaries. Similar patterns of attentional coselection were previously shown for combinations of space and color (Adamian, Slaustaite, & Andersen, ; Andersen et al, ; Hayden & Gallant, ) and orientation and color (Andersen et al, , ). Together, these findings strongly suggest that attentional facilitation is applied independently to the different task‐relevant dimensions or features that define the target stimulus, with the multiplicative effects of attention to each feature summing to produce maximal enhancement of the SSVEP to the target feature combination.…”
Section: Discussionsupporting
confidence: 81%
“…In the first study of exogenous FBA (Lin et al, 2011), participants detected the presence (Experiment 1) or discriminated the orientation (Experiment 3) of an oval in an array of uniquely colored circles appearing 200 ms after an uninformative precue was briefly presented. In most studies that manipulate endogenous FBA, a precue has been used as well (e.g., Adamian, Slaustaite, & Andersen, 2019;Fang, Becker, & Liu, 2019;Herrmann, Heeger, & Carrasco, 2012;Ling, Liu, & Carrasco, 2009;Liu et al, 2007b;McMains, Fehd, Emmanouil, & Kastner, 2007;Serences & Boynton, 2007;Störmer & Alvarez, 2014;White & Carrasco, 2011;White et al, 2015). Exogenous SA and exogenous FBA were probed by independently varying the precue's spatial location and color relative to the target ("valid" meaning matching that of the target, "invalid" meaning differing from the target).…”
mentioning
confidence: 99%
“…Despite robust SSVEP amplitude (Cohen's d > 5), we observed no credible evidence that the SSVEP response was higher for an attended versus unattended color in either cue condition. Positive control analyses revealed that our lack of SSVEP effect was not due to a complete lack of attention to the attended color: ERP responses (P3) to the targets were modulated by attention as expected (Adamian et al, 2019;Andersen et al, 2013;Andersen, Fuchs, et al, 2011). In light of our inconclusive results, we also performed a focused methodological review of key potential task differences between our work and prior work that may have resulted in our failure to detect the effect of feature-based attention on SSVEP amplitude.…”
Section: Introductionmentioning
confidence: 75%
“…We included trials where there was only one target or distractor event on that trial, to avoid the possibility of overlap between the two signals. We calculated P3 voltage at electrodes Pz and POz during the time window 450-700 ms after target onset, similar to prior work (Adamian et al, 2019;Andersen et al, 2013;Andersen, Fuchs, et al, 2011).…”
Section: Checking If a Priori Electrodes Are Reasonablementioning
confidence: 99%